Design of normalised and simplified FAs in quantum‐dot cellular automata. Issue 10 (25th October 2017) - Zhang, Yongqiang; Xie, Guangjun; Sun, Mengbo; Lv, Hongjun
Abstract : Quantum‐dot cellular automata (QCA), which is a burgeoning technique at nanoscale region to take the important place of complementary metal–oxide–semiconductor technology, has been studied for several years. The recent primary research emphasis is mainly focusing on circuit design, for instance, full adders (FAs) and multiplexers. The authors will present a new five‐input majority gate to construct FAs. Three QCA normalised FAs based on different logical expressions are then selected and designed, denoted as NFA1–NFA3, respectively. To conveniently compare with existing adders, three simplified FAs are also designed, named SFA1–SFA3. Analysis results indicate that SFA3 presents better performance in some extent.